Study of Flood Variation of Wainganga River Basin and Dhuti Dam with Impact on Crops at Balaghat Station (India) - Patle, S. K.; Parasar, C.; Chavan, R. (ASEAN Journal of Science and Engineering, 2023)
The usefulness of the Dhuti dam and its importance for crop irrigation at the Balaghat station, located on the Waingang River in Madhya Pradesh, India, has been the focus of research on rainfall fluctuations in the Wainganga sub-basin. Wainganga is the largest peninsular river in India. Wainganga River flows for 635.40 kilometers. Until its confluence with the Wardha River, the Wainganga River has a catchment area of 51,000 km2. The basin spans the five districts of Maharashtra and three districts of Madhya Pradesh. The Wainganga Basin is also mentioned in "The Jungle Book" by the famous writer Rudyard Kipling. The Wainganga Basin is known for the production of rice and, more specifically, Chinour. Balaghat "Chinour" rice obtained G-Tag certificate in 2021, and is now internationally renowned and exported. Rice crops are irrigated mainly by water from the Dhuti dam throughout the year. The dam is very important for the development of rice crops in the region. Sir Jorge, a British engineer, built the dam between 1911 and 1921. It is one of the oldest earthen dams in India, sealed with lime mortar. Floods have affected the cultivated area and water demand in the Balaghat district area for the past few years. The intensity and duration of rainfall varies from year to year along with changes in climatic conditions. The effect of flooding in a given season, as well as basin factors such as variations in rainfall, coefficient of variance, and agricultural damage were examined.